THE RELATIONSHIP BETWEEN TOXIC RELATIONSHIPS AND MENTAL HEALTH AMONG NON-LOCAL NURSING - Purnama, Sri; Sutejo, Sutejo; Puji Rahayu, Prastiwi (Jurnal Keperawatan Sriwijaya, 2026)
Aim: Mental health is an essential aspect influencing an individual’s ability to adapt and function optimally. Nursing students who study away from home are vulnerable to mental health problems due to academic pressure, limited social support, and involvement in toxic relationships that negatively affect psychological well-being. This study aimed to analyze the relationship between toxic relationships and mental health among nursing students living away from home from the 2024 cohort at Universitas ‘Aisyiyah Yogyakarta. Methods: This study employed a correlational design with a cross-sectional approach. The sample consisted of 108 nursing students living away from home, selected using a total sampling technique. Data were collected using a toxic relationship questionnaire and the Mental Health Continuum–Short Form (MHC-SF). Data analysis was conducted using the chi-square test. Results: Among the respondents, 49.1% experienced toxic relationships, while 50.9% did not. The distribution of mental health status showed that 51.9% of students had low mental health, whereas 40.1% had high mental health. The chi-square test results indicated a statistically significant relationship between toxic relationships and mental health (p = 0.004). Involvement in toxic relationships was associated with a decline in students’ mental health levels. Conclusion: There is a significant relationship between toxic relationships and mental health among nursing students living away from home.